Glycaemic control and its associated factors in Chinese adults with type 1 diabetes mellitus. Issue 8 (27th October 2015) - Liu, Li; Yang, Daizhi; Zhang, Yan; Lin, Shuo; Zheng, Xueying; Lin, Shaoda; Chen, Lishu; Zhang, Xiuwei; Li, Lu; Liang, Ganxiong; Yao, Bin; Yan, Jinhua; et al.
Abstract: Background: Glycaemic control is a great challenge in the management of type 1 diabetes mellitus (T1DM). There is limited data concerning glycaemic control among adults with T1DM. We used data from the Guangdong T1DM Translational Medicine Study to evaluate glycaemic control and its associated factors in Chinese adults with T1DM. Methods: This cross‐sectional analysis included 827 participants who were 18 years of age or older and had been living with T1DM for at least 1 year. Participants with HbA1c levels <7% were compared against those with HbA1c levels ≥ 7%. A multivariate logistic regression model was used to examine factors associated with glycaemic control. Results: Among the 827 participants, the mean age was 34.2 ± 12.1 years and the median (interquartile range) duration of diabetes was 6.1 (3.4, 10.4) years. The median HbA1c level was 8.5% (7.5%, 10.2%). Only one‐fifth of participants had HbA1c levels <7%. Insufficient glycaemic control (HbA1c ≥ 7%) was strongly associated with infrequent self‐monitoring of blood glucose (OR = 1.21, 95% CI 1.14 1.29, p = 0.000), high insulin dose (OR = 1.27, 95% CI 1.07 1.52, p = 0.006), smoking (OR = 3.11, 95% CI 1.44 6.72, p = 0.004), low‐frequency clinical visits (OR = 2.74, 95% CI 1.47 5.10, p = 0.001), the presence of diabetic autoantibodies (OR = 1.63, 95% CI 1.07 2.48, p = 0.022) and low fasting C‐peptide (FCP) levels (OR = 1.21, 95% CI 1.01 1.46, p = 0.049) after adjustment for age at disease onset, education level, household income and diet control. Conclusions: Most adult patients with T1DM did not achieve the HbA1c target. Identifying determinants for glycaemic control provides us valuable information to improve glycaemic control in these patients. Copyright © 2015 John Wiley & Sons, Ltd.